Pullout response of geogrids after installation - Pinho-Lopes, Margarida (2018)
Damage of geosynthetics during installation processes can affect their performance, so they are typically represented in design by applying reduction factors to their tensile strength measured in the laboratory. This paper contributes to better understanding whether this is representative of the pullout response of geogrids when confined in soil. The effects of installation damage induced in field trials of two extruded geogrids and one composite with a grid structure were studied. Pullout tests were used to characterise the impact of installation damage on the soil–geosynthetic interface interaction. The coefficients of interaction were analysed to assess the impact of different parameters, including the nominal strength of the geogrids and compaction energy applied. The coefficient of interaction was affected differently by installation, depending on both the geosynthetic and the soil in contact with it. Confinement in a soil with higher friction angle was more effective in mobilising the interface strength, for both undamaged and damaged samples. The type of soil in contact with the geosynthetics was more relevant for the interface strength than the normal stresses applied in the tests. The main lesson learned from this study is that the use of results from tensile strength of damaged materials to estimate the corresponding effects on their pullout response can lead to very conservative solutions.